IMPROVING YOUTHS SOCIAL SITUATION IN THE EUROPEAN UNION - G. Rtmbu; L. Constantinescu (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)

(untitled)
The European Unions social policies of the last years aimed at improving the social conditions of youths across Europe. The goal of this paper is to comparatively analyse the characteristics of youths and their social conditions in the EU-27, during 20062016, using the following indicators associated to the young population: youth education and training, employment and unemployment rates, health, social inclusion, culture and creativity, participation and youth in the digital world. The paper also reviews the impact and efficiency of the EUs social policies in the current economic background, trying to catch the improvements in young peoples social conditions. For this purpose, there were used Employment and Social Conditions Indicators and Europe 2020 Strategy Indicators. Our analysis reveals that over time the youths aspirations and needs have changed along with their social conditions. The EU is obviously making progress in improving the social policies addressed to young people, but there are still visible differences between the member states and new, innovative approaches are required to respond to youths needs in the fast-changing economic and political context of Europe.